EMOTIONAL PERCEPTION AND CULTURAL MOTIVATION ON LOYALTY TO A WORLD HERITAGE SITES DESTINATION - Jesús Claudio PEREZ GALVEZ; Pedro Antonio FUENTES JIMENEZ; Pablo RODRIGUEZ GUTIERREZ; Miguel Jesús MEDINA VIRUEL (Geo Journal of Tourism and Geosites, 2023)
The aim of this paper is to contribute to the scientific literature in the field of tourism in Latin America (Sucre, Bolivia was named a World Heritage Site (WHS) by UNESCO). This study analyses the relevance of the cultural motivation and emotional experience of the tourist to positively influence the image or the perceived value of the heritage site visited. The research shall also analyse other relationships, such as the positive effect of the perceived value on the loyalty of tourists and the influence of the visitor’s place of origin as a moderating variable in the formation of the image and loyalty to the destination. The analysis was performed by means of structural equation models (SEMs). The data were extracted through fieldwork consisting of interviews with visitors to the city. The results of the research revealed that the perceived value of a heritage destination not only depends on the functional and tangible aspects of the attributes but also on the emotional experience and cultural interest regarding the heritage site visited. Similarly, there is evidence of a relationship between perceived value and a loyal attitude and that it is moderated by the origin of the tourist, this being a great influence in the case of the domestic tourist.